Methods for determining the CO2 removal capacity of enhanced weathering in agronomic settings - Almaraz, Maya; Bingham, Nina L.; Holzer, Iris O.; Geoghegan, Emily K.; Goertzen, Heath; Sohng, Jaeeun; Houlton, Benjamin Z. (Frontiers in Climate, 2022)
Recent analysis by the IPCC suggests that, across an array of scenarios, both GHG emissions reductions and various degrees of carbon removal will be required to achieve climate stabilization at a level that avoids the most dangerous climate changes in the future. Among a large number of options in the realm of natural climate solutions, atmospheric carbon dioxide removal (CDR) via enhanced silicate weathering (EW) in global working lands could, in theory, achieve billions of tons of CO2 removal each year. Despite such potential, however, scientific verification and field testing of this technology are still in need of significant advancement. Increasing the number of EW field trials can be aided by formal presentation of effective study designs and methodological approaches to quantifying CO2 removal. In particular, EW studies in working lands require interdisciplinary ‘convergence’ research that links low temperature geochemistry and agronomy. Here, drawing on geologic and agronomic literature, as well as demonstration-scale research on quantifying EW, we provide an overview of 1) existing literature on EW experimentation as a CO2 removal technique, 2) agronomic and geologic approaches to studying EW in field settings, 3) the scientific bases and tradeoffs behind various techniques for quantifying CO2 removal and other relevant methodologies, and 4) the attributes of effective stakeholder engagement for translating scientific research in action. In doing so, we provide a guide for establishing interdisciplinary EW field trials, thereby advancing the verification of atmospheric CO2 in working lands through the convergence of geochemistry and agronomy.